Pattern and Outcome of Preterm Newborns Admiited to NICU Bacha Khan Medical Complex /Gajju Khan Medical Complex Swabi - Muhammad Tariq; Ahmad, Waqar; Haji Gul; Inayat Ullah; Hussain, Saddam; Rasool, Muhammad Farhan (Indus Journal of Bioscience Research, 2025)
Prematurity remains a leading contributor to neonatal morbidity and mortality, particularly in low-resource countries such as Pakistan. Despite improvements in neonatal intensive care services, preterm infants continue to experience high rates of adverse outcomes. Identifying local determinants of neonatal morbidity and mortality is essential for targeted interventions. To determine the spectrum of morbidities and predictors of clinical outcomes among preterm neonates admitted to the Neonatal Intensive Care Unit (NICU) of Bacha Khan Medical Complex, Swabi.This prospective cohort study was conducted over 18 months (January 2024-June 2025) and included 221 preterm neonates (